Emergence of realism: Enhanced visual artistry and high accuracy of visual numerosity representation after left prefrontal damage - Takahata, Keisuke; Saito, Fumie; Muramatsu, Taro; Yamada, Makiko; Shirahase, Joichiro; Tabuchi, Hajime; Suhara, Tetsuya; Mimura, Masaru; Kato, Motoichiro (Neuropsychologia, 2014)
Over the last two decades, evidence of enhancement of drawing and painting skills due to focal prefrontal damage has accumulated. It is of special interest that most artworks created by such patients were highly realistic ones, but the mechanism underlying this phenomenon remains to be understood. Our hypothesis is that enhanced tendency of realism was associated with accuracy of visual numerosity representation, which has been shown to be mediated predominantly by right parietal functions. Here, we report a case of left prefrontal stroke, where the patient showed enhancement of artistic skills of realistic painting after the onset of brain damage. We investigated cognitive, functional and esthetic characteristics of the patient׳s visual artistry and visual numerosity representation. Neuropsychological tests revealed impaired executive function after the stroke. Despite that, the patient׳s visual artistry related to realism was rather promoted across the onset of brain damage as demonstrated by blind evaluation of the paintings by professional art reviewers. On visual numerical cognition tasks, the patient showed higher performance in comparison with age-matched healthy controls. These results paralleled increased perfusion in the right parietal cortex including the precuneus and intraparietal sulcus. Our data provide new insight into mechanisms underlying change in artistic style due to focal prefrontal lesion. •We described the case of enhanced visual realism after the stroke in the left frontal cortex.•Enhanced realism was accompanied by superior performance of visual numerical cognition.•The patients showed increased perfusion in the right parietal cortex.